Establishment of a Multivariate Analysis Based on Photonic Crystal Hydrogel Bead Arrays and Its Application for Detecting Platelet-specific Antibodies. (24th May 2018) - Kong, Xin; Guo, Yanting; Ling, Yun; Chen, Baoan
ABSTRACT: Photonic crystals are nanomaterials with unique structural coloration, and they have been used in multiple analyses, gene function analyses, and nanoarray biosensors. Here, we used agarose hydrogel microcarriers with characteristic reflection peak codes to improve the biocompatibility of the material and the efficiency of detection, which may be helpful for further clinical applications. The paper has two parts: condition optimization and product application. Goat antihuman immune globulin G, human immune globulin G, and fluorescein isothiocyanate-labeled goat antihuman immune globulin G are commonly used materials in double-antibody sandwich techniques, which are used for optimization in the application of advanced composite materials. Goat antihuman immune globulin G was immobilized on the surfaces of photonic crystal hydrogel beads through chemical bonding. When the target immune globulin G was captured, the fluorescence-labeled antibody could combine with photonic crystal hydrogel beads. The reaction conditions were optimized using the gray-scale value of fluorescent intensities. Photonic crystal hydrogel beads with different reflection spectra were coated with purified platelet glycoprotein IIb/IIIa and glycoprotein Ib/IX. A total of 64 clinical samples including sera from patients with immune thrombocytopenia ( n  = 32) and healthy human sera ( n  = 32) were tested using photonic crystal hydrogel beads and monoclonal antibody immobilization of platelet antigen (MAIPA). Photonic crystal hydrogel bead array reaction conditions were established for multiple analysis, showing similar sensitivity and specificity with MAIPA in testing different platelet antibodies and shortening the analysis time. The features of these composite materials make them suitable for potential applications in clinical screening assays.